1976
DOI: 10.1152/ajplegacy.1976.230.1.239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acid lumen pH on potassium transport in renal cortical collecting tubules

Abstract: In order to determine the effect of acid lumen pH on renal tubular potassium transport, cortical collecting tubules were dissected from rabbit kidneys and perfused in vitro. When the pH of the perfusate was lowered from 7.4 to 6.8, potassium secretion into the tubule lumen decreased by an average of 47%. The transepithelial voltage increased from a mean value of -32 mV (lumen negative) at pH 7.4 to -51 mV at PH 6.8. Net sodium absorption from the tubule lumen was essentially unchanged (5% mean decrease). Trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 0 publications
3
21
0
Order By: Relevance
“…11 26 transepithelial Na ϩ flux was unaffected by changes in luminal pH. Similarly, Na ϩ absorption in the superficial distal tubule was unchanged after a 1-hour infusion of NaHCO 3 .…”
Section: Absorption Of Namentioning
confidence: 86%
“…11 26 transepithelial Na ϩ flux was unaffected by changes in luminal pH. Similarly, Na ϩ absorption in the superficial distal tubule was unchanged after a 1-hour infusion of NaHCO 3 .…”
Section: Absorption Of Namentioning
confidence: 86%
“…Another factor responsible for the increased K excretion might be the increased amounts of HCO3 in the distal tubule which would behave as a nonreabsorbable anion further increasing luminal negativity leading to increased K secretion (53,57). Fi.rthermore, K secretion in the cortical collecting tubule has been shown to increase when the luminal pH is raised (58). Finally, increased…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies on the isolated perfused CCT of the rabbit have demonstrated the existence of active potassium secretion in this segment (23)(24)(25)(26)(27). The ability of patients and experimental animals with renal disease to maintain potassium homeostasis despite significant reductions on functioning renal mass (1,4,(14)(15)(16)(17)(18)(19)(20)(21)(22)(28)(29)(30)(31)(32) suggests that nephron sites which normally secrete potassium are able to augment this secretion to maintain potassium balance in chronic uremia.…”
Section: Discussionmentioning
confidence: 99%